2015
DOI: 10.1136/bmjopen-2014-006812
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PaO2/FiO2for stratification of patients with moderate and severe acute respiratory distress syndrome

Abstract: ObjectivesA recent update of the definition of acute respiratory distress syndrome (ARDS) proposed an empirical classification based on ratio of arterial partial pressure of oxygen to fraction of inspired oxygen (PaO2/FiO2) at ARDS onset. Since the proposal did not mandate PaO2/FiO2 calculation under standardised ventilator settings (SVS), we hypothesised that a stratification based on baseline PaO2/FiO2 would not provide accurate assessment of lung injury severity.DesignA prospective, multicentre, observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 36 publications
8
90
0
5
Order By: Relevance
“…In our study, diagnostic criteria for ARDS must be met in two consecutive days to get a more consistent diagnosis. This is supported by recent reports [20,21]. In an observational study, the use of a standardized ventilatory setting at 24 h of ARDS onset allowed a more precise and clinically relevant stratification of ARDS patients [20].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In our study, diagnostic criteria for ARDS must be met in two consecutive days to get a more consistent diagnosis. This is supported by recent reports [20,21]. In an observational study, the use of a standardized ventilatory setting at 24 h of ARDS onset allowed a more precise and clinically relevant stratification of ARDS patients [20].…”
Section: Discussionsupporting
confidence: 61%
“…In an observational study, the use of a standardized ventilatory setting at 24 h of ARDS onset allowed a more precise and clinically relevant stratification of ARDS patients [20]. And, in other large, observational study demonstrated that risk stratification of ARDS patients based on PaO2/FiO2 recorded at ARDS onset (baseline) is not clinically useful [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, it becomes difficult-if not impossible-to interpret trial results [11]. Villar et al [18] studied 478 patients with moderate and severe ARDS and examined the PaO 2 /FiO 2 at ARDS onset, after 24 h of usual care, and at 24 h under standardized ventilator settings. Their standardized model outperformed the Berlin criteria and non-standardized PaO 2 /FiO 2 at 24 h. More than 60 % of patients with severe ARDS according to Berlin criteria were reclassified as moderate, mild or non-ARDS after 24 h of usual care, while hospital mortality changed significantly with every PaO 2 /FiO 2 category under the standardized method.…”
Section: Searching For a Satisfactory Ards Definitionmentioning
confidence: 99%
“…However, no simple and reliable index quantifying the clinical condition of ARDS patients predicts hospital outcome at 24 hours of usual care (including lung protective ventilation and hemodynamic stabilization) until the recent description and validation of an ARDS score by Villar et al (5). Current definitions of ARDS are incapable of properly identifying or stratifying ARDS patients in terms of severity and prognosis (4). It is increasingly recognized that our understanding of the definition of ARDS and its outcome has been limited by the failure to accept that ARDS is a syndrome with different phenotypes that are independent of each other (1,4).…”
Section: Introductionmentioning
confidence: 99%